Identification and validation of reference genes for gene expression study using Quantitative Real-Time PCR in shallot (Allium cepa L. Aggregatum group) based on bulb development phase - ENDANG SULISTYANINGSIH; WIDHI DYAH SAWITRI; VALENTINA DWI SUCI HANDAYANI; ADDIN WAHYU WICAKSONO; CLARENCIA MARGARETH SILALAHI; RUDI HARI MURTI (Society for Indonesian Biodiversity, 2024)
Abstract. Sulistyaningsih E, Sawitri WD, Handayani VDS, Wicaksono AW, Silalahi CM, Murti RH. 2024. Identification and validation of reference genes for gene expression study using Quantitative Real-Time PCR in shallot (Allium cepa L. Aggregatum group) based on bulb development phase. Biodiversitas 25: 2645-2651. Shallot (Allium cepa L. Aggregatum group) is cultivated vegetatively using bulbs (produce many bulbs) and generatively using TSS (True Seed of Shallot) which tends to produce single bulbs. Bulb aggregation is influenced by activity of genes and the gene expression could be analyzed using quantitative Real-Time Polymerase Chain Reaction (qRT-PCR). The qRT-PCR analysis requires reference gene data (housekeeping gene) as a comparison gene against our target gene. This study aimed to select and validate three housekeeping genes in shallot as an initial study for qRT-PCR analysis. The research flow began with the preparation of shallot 'TukTuk' leaves and bulb samples in bulb formation from bulb initial phase to mature phase. Furthermore, a specific primer design based on actin, tubulin, and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene sequences were obtained from gene bank data. The results showed that the actin, tubulin, and GAPDH genes were successfully amplified and the products were 142 bp, 116 bp, and 136 bp in size, respectively and the genes were expressed almost constantly in leaves and bulbs in all phases of bulb formation. The tubulin gene had the potential as a reference gene for qRT-PCR analysis in shallot with the most consistently expressed.